THE INFLUENCE OF ADVERTISING ON INSTAGRAM SOCIAL MEDIA AND CELEBRITY ENDORSEMENT ON PURCHASE INTEREST IN DEAR ME BEAUTY PRODUCTS - Amilia, Suri; Lindung Bulan, Tengku Putri; Dewi, Meutia (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2024)
This research aims to determine the effect of advertising on Instagram social media and celebrity endorsements on purchasing interest in Dear Me Beauty products in Langsa City. This research used a sample of 96 respondents with the criteria for respondents who used Dear Me Beauty products in the Langsa City area and were aged 17 years and over. The data analysis method uses multiple linear regression, t-test, F test, and coefficient of determination test (Adjusted R2). The results of the t-test state that the advertising variable on Instagram social media has a significant effect on buying interest in Dear Me Beauty products in Langsa City, and the celebrity endorsement variable has a significant impact on buying interest in Dear Me Beauty products in Langsa City. The results of the F test state that advertisements on Instagram social media and celebrity endorsements simultaneously significantly affect purchasing interest in Dear Me Beauty products in Langsa City. Keywords: Advertising on Instagram Social Media, Celebrity Endorsement, Buying Interest.